Skype Video congestion control: An experimental investigation - Luca De Cicco; Saverio Mascolo; Vittorio Palmisano (Computer Networks, 2011)
The Internet is facing a significant evolution from being a delivery network for static content to an efficient platform for multimedia content delivery. Well-known examples of applications driving this evolution are YouTube Video on Demand, Skype Audio/Video conference, IPTV and P2P video distribution. While YouTube streams videos using the Transmission Control Protocol (TCP), time-sensitive applications, such as Skype Audio/Video conference, employ the UDP because they can tolerate small loss percentages but not delays due to TCP recovery of lost packets via retransmissions. Since, differently from the TCP, the UDP does not implement congestion control, these applications must implement congestion control at the application layer in order to avoid congestion and preserve network stability. In this paper we investigate Skype Video congestion control in order to assess to what extent this application is able to throttle its sending rate to match the unpredictable Internet bandwidth while preserving resource for co-existing best-effort TCP traffic. We have found that: (1) Skype Video adapts its sending rate by varying frame rate, frame quality and video resolution; (2) in many scenarios a Skype Video call refrains from fully utilizing all available bandwidth thus not sending videos at the highest possible quality; (3) Skype Video employs an adaptive FEC action that is proportional to the experienced loss rate; (4) the sending rate matches a changing available bandwidth with a transient time as large as a hundred of seconds; (5) the minimum bandwidth required for a video call is 40kbps at 5 frames per second.
Keywords: Congestion control; Skype Video